Adalimumab in Pediatric Inflammatory Bowel Disease - Choi, So Yoon; Kang, Ben (Frontiers in Pediatrics, 2022)
The introduction of biological agents with strong anti-inflammatory action, such as antitumor necrosis factor (TNF) agents, has greatly contributed to changes in inflammatory bowel disease (IBD) treatment strategy and goals, which is advantages for the long-term prognosis of patients. Moreover, several biological agents are being used or researched in pediatric populations. However, only two biological agents, namely infliximab (IFX) and adalimumab (ADL), have currently been approved for children and adolescents. In pediatric IBD, there are limitations and burdens associated with facilitating mucosal healing (MH) when utilizing these two biological agents. ADL is effective in both naïve patients and those with previous experience with biologics. Beyond clinical remission, this drug is also effective for MH and histological remission. The use of therapeutic drug monitoring to further enhance the effectiveness of ADL treatment can be expected to reduce treatment failure of ADL and pave the way for appropriate treatment in the treat-to-target era. This review paper focuses on ADL, examine studies conducted in children, and determine the role this agent plays against pediatric inflammatory bowel disease.